Pengaruh Kecerdasan Intelektual Dan Kecerdasan Spiritual Terhadap Kinerja Karyawan : (Survei Pada Karyawan Non Manajer Grand Metro Hotel Tasikmalaya) - Asri Nurhayati (CV. ULIL ALBAB CORP, 2022)
This study aims to determine and analyze the influence of intellectual intelligence partially on the performance of non-manager employees at Grand Metro Hotel Tasikmalaya and the influence of partial intelligence on the performance of non-manager employees at Grand Metro Hotel Tasikmalaya. The method used in this study is a survey with a quantitative approach. With a study sample of 32 Back Office employees as respondents. The data used is using primary data. The analysis tool used in this study is multiple linear regression using the SPSS support application version. 20. Based on the data that have met the validity test, reliability test and classical assumption test are processed so as to produce the following regression equation: Y=8.989+0.216X_1+0.735 X_2. The test results showed that it partially showed that the variables used in the study, namely intellectual intelligence and spiritual intelligence, had a significant effect on employee performance at the Grand Metro Hotel Tasikmalaya. Simultaneously there was a positive and significant influence of intellectual intelligence and spiritual intelligence together on the performance of non-manager employees based on multiple linear regression analysis tests obtained by a calculation of 108,204 significations of 0.000. By testing the Coefficient of Determination to get an R Square value of 0.783 or 78.30%. shows the magnitude of the influence of intellectual intelligence and spiritual intelligence on employee performance and 21.70% is the influence of other variables beyond the variables used in this study.